Efektivitas metode case-based concept map untuk meningkatkan pemahaman patofisiologi dan perilaku caring mahasiswa keperawatan - Pratiwi, Hikmi Muharromah; Nani, Desiyani (Holistik Jurnal Kesehatan, 2025)
Background: Adequate understanding of pathophysiology is essential for nursing students to provide competent care and demonstrate caring behavior towards patients. In addition, caring behavior is at the core of the nursing care process. Concept maps, a visual learning strategy, have shown promise in facilitating the understanding of pathophysiology and may positively impact on improving caring behavior among nursing students. Purpose: To analyze the effectiveness of the case-based concept map method in improving the understanding of pathophysiology and caring behavior of nursing students. Method: A quasi-experimental study with a pre-posttest with control group approach on 149 nursing students (intervention group: 81 participants, control group: 68 participants) in May - July 2024. The application of the concept map was carried out for 5 weeks in the intervention group. This study used the Caring Behavior Inventory (CBI) questionnaire to measure students' caring behavior and a quiz to measure students' understanding of pathophysiology which was filled out online. The analysis in this study used paired t-test and independent t-test. Results: The mean score difference in pathophysiology understanding between the intervention group and the control group was significantly higher in the intervention group (p = 0.000, t = 3.882). In contrast, the mean score of caring behavior did not show a significant difference between the intervention and control groups (p = 0.37, t = 0.899). Conclusion: The case-based concept map is effective in enhancing the understanding of pathophysiology; however, this method remains inconsistent in promoting the caring behaviors of nursing students. Suggestion: Future research is expected to develop an extended case-based concept map application in nursing process planning (formulation of nursing diagnoses, determination of outcome criteria, and selection of nursing interventions) in nursing students at the final level or nursing students who are carrying out learning in clinical practice.   Keywords: Concept Map; Caring Behavior; Nursing Students; Pathophysiology.   Pendahuluan: Pemahaman yang adekuat tentang patofisiologi sangat penting bagi mahasiswa keperawatan untuk memberikan perawatan yang kompeten dan menunjukkan perilaku caring kepada pasien. Selain itu, perilaku caring merupakan inti dari proses asuhan keperawatan. Concept map merupakan sebuah strategi pembelajaran visual, terbukti menjanjikan dalam memfasilitasi pemahaman patofisiologi dan mungkin berdampak terhadap peningkatan perilaku caring pada mahasiswa keperawatan. Tujuan: Untuk menganalisis efektivitas metode case-based concept map dalam meningkatkan pemahaman patofisiologi dan perilaku caring mahasiswa keperawatan. Metode: Penelitian studi quasi eksperimental dengan pendekatan pre-posttest with control group pada 149 mahasiswa Jurusan Keperawatan (kelompok intervensi: 81 partisipan, kelompok kontrol: 68 partisipan) pada bulan Mei – Juli 2024. Penerapan concept map dilakukan selama 5 minggu pada kelompok intervensi. Penelitian ini menggunakan kuesioner Caring Behavior Inventory (CBI) untuk mengukur perilaku caring mahasiswa dan kuis untuk mengukur pemahaman patofisiologi mahasiswa yang diisi secara online. Paired-t-test dan independent t-test digunakan untuk analisis dalam penelitian ini. Hasil: Perbedaan rerata skor pemahaman patofisiologi pada kelompok intervensi lebih tinggi secara signifikan dibandingkan skor rerata pada kelompok kontrol (p = 0.000, t = 3.882). Sedangkan, rerata skor perilaku caring antara kelompok intervensi dan kontol tidak berbeda secara signifikan (p = 0.37, t = 0.899). Simpulan: Case-based concept map efektif dalam meningkatkan pemahaman patofisiologi. Namun, metode ini masih belum inkonsisten dalam meningkatkan perilaku caring mahasiswa keperawatan. Saran: Penelitian selanjutnya diharapkan dapat mengembangkan aplikasi case-based concept map yang diperluas dalam perencanaan proses keperawatan (perumusan diagnosa keperawatan, penentuan kriteria luaran, dan pemilihan intervensi keperawatan) pada mahasiswa keperawatan.   Kata Kunci: Concept Map; Mahasiswa Keperawatan; Patofisiologi; Perilaku Caring.